Prevalence of breast cancer in reduction mammoplasty specimens, in women of African origin: preliminary histology results at Mankweng and Polokwane hospitals: Clinical Case Series. - Mzezewa, Salathiel Zhou; Setati, Musa; Netshiongolwe, Thendo; Sinoamadi, Vusani (Jour Med Resh and Health Sci, 2020)
Abstract Introduction. We report the first study on the prevalence of breast cancer in reduction mammoplasty specimens conducted in Limpopo province, South Africa. The prevalence of breast cancer is relatively low among pre-menopausal African women. Worldwide prevalence has been reported to range between 0.1% and 4.5%. Patients requesting reduction mammoplasty fear that their breast enlargement may be caused by the disease. Reduction mammoplasty is a common operation performed by plastic and reconstructive surgeons globally, but is an uncommon operation in Limpopo. Aims and objectives. To determine the prevalence of breast cancer in reduction mammoplasty specimens and to record the pertinent characteristics. Method. A prospective study of 104 female patients requesting reduction mammoplasty from 2007–2014 at Polokwane and Mankweng hospitals. The outcome measures were weight of specimens and histological investigation for breast carcinoma, body mass index and jugular–nipple distances. Results. All patients were of African origin whose median age was 32.4 (16–53) years, and median weight of excised tissue was 3.4 (1.45–6.2) kg. The median weight of patients was 77 (63–92) kg. The median BMI was 34.5 (29.1–39.9) kg/m2. The median jugular–nipple distance was 39 (25–51) cm on the right and 41 (29–53) cm on the left breast. Histological investigation revealed normal breast tissue in 57 cases, fibroadenosis in 25 cases, and duct hyperplasia in 22 cases. Conclusion. Breast cancer was not detected. The study population was relatively young at a mean age of 32.4 (16–53) years, without personal nor family history of breast cancer.